The predominance of nucleotidyl activation in bacterial phosphonate biosynthesis - Kyle Rice (Nature Portfolio, 2019)
Phosphonate modifications can be present on microbial cell surfaces. Here the authors perform bioinformatics analyses and observe a widespread occurrence of nucleotidyltransferase-encoding genes in bacterial phosphonate biosynthesis and functionally characterize two of the identified phosphonate specific cytidylyltransferases (PntCs) and determine the crystal structure of T. denticola PntC.